AN ERROR ANALYSIS ON PROCEDURE TEXT WRITTEN BY THE 11TH STUDENT OF SMA NEGERI 1 PURWODADI - ARIWIBOWO, PUJI (2011)
This study is aimed at 1) describing the type of error made in the procedure text written by the 11th students of SMA Negeri 1 Purwodadi, 2) identifying the source of error. In achieving the objectives, the researcher used qualitative content analysis research as the approach to collect and analyze the data. The research was held in SMA N 1 Purwodadi. The research took 33 students of the second year students (XI IPA 2) as the subject of the study. The writer gets the data of the research by giving a test to make a procedure text to the 11th students of SMA Negeri 1 Purwodadi. The techniques for analyzing data are: 1) collecting the data, 2) identifying the error, 3) classifying the data, 4) describing the error, and 5) drawing conclusion. The result of the analysis shows that the student of SMA Negeri 1 Purwodadi makes four types of error. They are omission error, addition error, misformation error, and misordering error. Omissions error is most frequently error made by the students with 197 data or 59,7%. The second is addition error with 72 data or 21,8% that consist of simple addition with 68 data or 20,6% and double marking with 4 data or 1,2 %. The third is misformation error with 47 data or 14,2% that consist of archi-form with 42 data or 12,7% and regularization with 5 data or 1,5%. The last is misordering with 14 data or 4,2%. And the writer finds two sources of errors. They are interlingual and intralingual transfer. This research shows that the students still make errors in writing procedure text and they need improvement to develop their skill especially in writing procedure text.